Effect of Maternal Antidepressant Use During the Pre-pregnancy/Early Pregnancy Period on Congenital Heart Disease: A Prospective Cohort Study in Central China - Sun, Mengting; Zhang, Senmao; Li, Yihuan; Chen, Letao; Diao, Jingyi; Li, Jinqi; Wei, Jianhui; Song, Xinli; Liu, Yiping; Shu, Jing; Wang, Tingting; Huang, Peng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: With the increase in maternal antidepressant prescribing before/during pregnancy, concerns about the safety of antidepressants have come into focus. The purpose of this study was to explore the association between maternal antidepressant use before pregnancy/in early pregnancy and the risk of congenital heart disease (CHD) in children, and to provide a scientific basis for clinical safety of antidepressant use. Methods： The prospective cohort study ultimately included 34,104 singleton pregnancies. Modified Poisson regression model with robust error variances was used to evaluate RRs and 95% confidence intervals (CIs) for the risk of CHD in offspring exposed to maternal antidepressant in the 3 months before pregnancy and early pregnancy. In addition, sensitivity analysis was further performed to explore the robustness of the results. Results： In this study, the maternal antidepressant exposure rate was 2.83% in the 3 months before pregnancy, 2.42% in early pregnancy, and the incidence of CHD was 8.973 per 1000 live births. We found that maternal antidepressant use in the 3 months before pregnancy and early pregnancy were all associated with an increased risk of CHD, approximately 2.54 times and 2.87 times, respectively, of non-use of antidepressants after adjusting for potential confounders. This association was also found in CHD specific phenotypic analysis. Of these, offspring whose mothers were exposed to antidepressants in the 3 months before pregnancy had the highest risk of transposition of the great arteries (aOR=5.50, 95%CI: 1.91-15.88). The offspring of mothers exposed to antidepressants in early pregnancy had the highest risk of developing ventricular septal defect (aOR=4.80, 95% CI: 2.50-9.24). Sensitivity analysis verified the stability of the results. Conclusions: Maternal antidepressant use in the 3 months before pregnancy and early pregnancy were all associated with an increased risk of CHD in their offspring. In order to reduce the risk of teratogenesis, we recommend that pregnant women prepare for pregnancy after their condition improves or receive the minimum effective dose of medication.